2021
DOI: 10.1016/j.asmr.2021.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Patient-Reported Outcomes Measurement Information System Computerized Adaptive Testing (PROMIS CAT) Scores Predict Achievement of Minimum Clinically Important Difference Following Anterior Cruciate Ligament Reconstruction Using an Anchor-Based Methodology

Abstract: To determine the change in Patient-Reported Outcomes Measurement Information System Computerized Adaptive Testing (PROMIS CAT) scores for physical function, pain interference, and depression that constitute minimum clinically important difference (MCID) using an anchor-based technique and to identify pre-operative clinical thresholds in anchor-based MCID that predict likelihood of achieving MCID following anterior cruciate ligament (ACL) reconstruction. Methods: Adult patients aged 18 years or older undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…With the increasing utility of PROMs in evaluating orthopaedic patients, a number of different thresholds have been assigned to confer “clinical relevance.” Of these, the MCID is among the most common, but the heterogeneity of its determination and its dependence on preoperative scores represent significant limitations. 11 , 20 , 36 The present study found that the MCID-PF was affected only by preoperative PROMIS scores when using a previously reported 0.5 standard deviation–based MCID of 4.6, which was consistent with a recently published anchor-based MCID of 4.5 11 , 38 Thus, patients who have exceedingly low preoperative scores may achieve clinical success according to the MCID, but they may have inferior outcomes relative to their specific population and may not consider their result a success. Conversely, patients who have higher preoperative outcome scores may not achieve the MCID despite having a satisfactory outcome.…”
Section: Discussionsupporting
confidence: 91%
“…With the increasing utility of PROMs in evaluating orthopaedic patients, a number of different thresholds have been assigned to confer “clinical relevance.” Of these, the MCID is among the most common, but the heterogeneity of its determination and its dependence on preoperative scores represent significant limitations. 11 , 20 , 36 The present study found that the MCID-PF was affected only by preoperative PROMIS scores when using a previously reported 0.5 standard deviation–based MCID of 4.6, which was consistent with a recently published anchor-based MCID of 4.5 11 , 38 Thus, patients who have exceedingly low preoperative scores may achieve clinical success according to the MCID, but they may have inferior outcomes relative to their specific population and may not consider their result a success. Conversely, patients who have higher preoperative outcome scores may not achieve the MCID despite having a satisfactory outcome.…”
Section: Discussionsupporting
confidence: 91%
“…A systematic search of the PubMed/MEDLINE databases was used to identify studies examining PROMIS assessments in orthopaedic surgery patients. Studies were included in the anchor-based analyses if they calculated anchor-based thresholds for PROMIS Physical Function for THA, TKA, PLF, ACLR, and APM or the PROMIS Upper Extremity for TSA and RCR [3, 10-12, 16, 18, 23, 24, 29, 34, 37].…”
Section: Methodsmentioning
confidence: 99%
“…Because previous studies have found associations between preoperative PROs and outcomes after ACLR, a subset of patients with complete PRO data were analyzed in the current study. 35,45 Analysis of the subset of patients with PRO data demonstrated similar findings of age and sex being associated with knee extensor LSI, yet PROs were not associated with knee extensor LSI and did not impact previous associations. Finally, there are variables that were not assessed that could influence the results of the study.…”
Section: Limitationsmentioning
confidence: 77%